Insight into the formation mechanism of graphene quantum dots and the size effect on their electrochemical behaviors1. Issue 21 (7th June 2015) - Liu, Yonghuan; Wang, Rutao; Lang, Junwei; Yan, Xingbin
<x xml:space="preserve">Abstract</x> The formation mechanism of graphene quantum dots was studied, which showed a superior electrochemical performance and an ultra-high power response.